Forging a Healthier Future: Reflections on the Global Rural Health Summit - Kumar, Pratyush (Journal of Surgical Specialties and Rural Practice, 2025)
Abstract The echoes of vibrant discussions and collaborative energy still resonate following the recent Global Rural Health Summit. This landmark event served not only as a crucial follow-up to the productive Pre-Summit Rural WONCA Council Meeting on the 3rd but also as a powerful testament to the collective commitment of a diverse group of stakeholders - from family physicians and medical students to policymakers, nurses, and midwives - in addressing the pressing challenges and exciting opportunities within rural healthcare systems worldwide.